2003
DOI: 10.1021/jp035748t
|View full text |Cite
|
Sign up to set email alerts
|

Improved Formulas for the Calculation of the Electrostatic Contribution to the Intermolecular Interaction Energy from Multipolar Expansion of the Electronic Distribution

Abstract: We have, within the framework of the molecular mechanics method SIBFA, improved the formulation of the Coulomb (electrostatic) energy contribution to the intermolecular interaction energy. This was done by integrating "overlap-like" terms into two components of the multipolar development used to calculate this contribution in SIBFA. The calibration of the new component is done on five water dimers by fitting this augmented electrostatic contribution to the corresponding Ec term. Several tests are done on (i) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
210
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

7
2

Authors

Journals

citations
Cited by 145 publications
(212 citation statements)
references
References 37 publications
2
210
0
Order By: Relevance
“…By using this type of auxiliary basis, SCC-DFTB avoids the need for computing threeand four-center electron repulsion integrals, and Mulliken partitioning allows for the rapid construction of the auxiliary density from the atomic orbital (AO) density matrix through spline evaluation of the precomputed overlap matrices; however, this crude representation of the response density can have adverse effects on electrostatic interactions. 21 In general, accurate electrostatics are important for intermolecular 22,23 Variations of the SCC-DFTB method have been applied to water clusters, 24 liquid water, 24 and organic molecules, 6 and limitations in hydrogen bonding were noted in many cases, although it is difficult to directly attribute these deficiencies solely to the electrostatic description.…”
Section: Introductionmentioning
confidence: 99%
“…By using this type of auxiliary basis, SCC-DFTB avoids the need for computing threeand four-center electron repulsion integrals, and Mulliken partitioning allows for the rapid construction of the auxiliary density from the atomic orbital (AO) density matrix through spline evaluation of the precomputed overlap matrices; however, this crude representation of the response density can have adverse effects on electrostatic interactions. 21 In general, accurate electrostatics are important for intermolecular 22,23 Variations of the SCC-DFTB method have been applied to water clusters, 24 liquid water, 24 and organic molecules, 6 and limitations in hydrogen bonding were noted in many cases, although it is difficult to directly attribute these deficiencies solely to the electrostatic description.…”
Section: Introductionmentioning
confidence: 99%
“…This disadvantage has been addressed to an extent by the use of damping functions that correct the interaction energies at close intermolecular distances. [14][15][16] It has been shown that another possibility for the accurate determination of the intermolecular Coulomb contribution is by interacting the unperturbed frozen densities of the two molecules either numerically 17 or analytically. 18 The latter method is based on the density fitting (DF) formalism (Coulomb fitting), [19][20][21] where the electron density is expanded using Gaussian auxiliary basis sets (ABSs) centered on specific sites on the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…All results are compared to reference values calculated with CSOV. 15,23 In addition, the Coulomb interaction energy for a set of water boxes of increasing size is calculated to predetermined accuracy using reciprocal space methods and timing results are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…This shortcoming may be overcome to an extent by using damping functions that correct the intermolecular interaction energy. 18,19 Equation (1) can also be solved without approximations with either numerical or analytical procedures. Gavezzotti has proposed a method that relies on the direct numerical integration over molecular electron density.…”
Section: Introductionmentioning
confidence: 99%